iPods -a surrogate coach for junior and subelite athletes: new ideas based on a review of the literature - Harris, B. A. (The Journal of Strength and Conditioning Research, 2010)
The global proliferation of MP3 players such as iPods means coaches have an opportunity to access a tool to enhance coaching that much of the population already use widely, without considerable increase in investment of time or money. Research evidence strongly indicates that music has the ability to influence psychological and physiological factors and can improve performance measures significantly. Additionally, the nature of athlete's self-talk could possibly be influenced through the use of `digiprompts,` resulting in more focused and productive training sessions. Research evidence also indicates a limited effect on athlete adaptation during unsupervised training sessions related to decreased training frequency and intensity. Coaches should always look for ways to enhance their coaching, but new technologies and methodologies will only be widely accepted if seen by the coaching community as readily accessible and able to facilitate efficient improvement in coaching methodologies and athlete development. With technological advances in music delivery systems and digital editing, digital media and delivery systems for distance coaching should be explored. This paper reviews several fields of research in an attempt to highlight how the use of what is now common digital technology can create a `surrogate coach.` Through the development of structured and specific digital training aids, the effects of music as an ergogenic aid means the use of MP3 players seems a logical step forward for coaches, and unsupervised training could potentially be made more effective.